A Description of Vibrational Modes in Hexaphyrins: Understanding the Aromaticity Reversal in the Lowest Triplet State. Issue 39 (11th August 2016) - Sung, Young Mo; Oh, Juwon; Naoda, Koji; Lee, Taegon; Kim, Woojae; Lim, Manho; Osuka, Atsuhiro; Kim, Dongho
Abstract: Aromaticity reversal in the lowest triplet state, or Baird's rule, has been postulated for the past few decades. Despite numerous theoretical works on aromaticity reversal, experimental study is still at a rudimentary stage. Herein, we investigate the aromaticity reversal in the lowest excited triplet state using a comparable set of [26]‐ and [28]hexaphyrins by femtosecond time‐resolved infrared (IR) spectroscopy. Compared to the relatively simple IR spectra of [26]bis(rhodium) hexaphyrin (R26H ), those of [28]bis(rhodium) hexaphyrin (R28H ) show complex IR spectra the region for the stretching modes of conjugated rings. Whereas time‐resolved IR spectra ofR26H in the excited triplet state are dominated by excited state IR absorption peaks, while those ofR28H largely show ground state IR bleaching peaks, reflecting the aromaticity reversal in the lowest triplet state. These contrasting IR spectral features serve as new experimental aromaticity indices for Baird's rule. Abstract : Good vibrations : Using vibrational spectroscopy and quantum mechanical calculations, the contrasting IR spectral features in the lowest triplet and ground states provide new experimental evidence for aromaticity reversal in [26]‐ and [28]hexaphyrins.